Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.6 - Special Products - Exercise Set: 48



Work Step by Step

$(3x^{2}+1)(3x^{2}-1)$ To evaluate this product, use the following formula: $(a-b)(a+b)=a^{2}-b^{2}$ Here, $a=3x^{2}$ and $b=1$ $(3x^{2}+1)(3x^{2}-1)=(3x^{2})^{2}-1^{2}=9x^{4}-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.